Carbon nanotube/PVA aerogels impregnated with PEI: solid adsorbents for CO2 capture. Issue 7 (7th June 2018) - Gromov, A. V.; Kulur, A.; Gibson, J. A. A.; Mangano, E.; Brandani, S.; Campbell, E. E. B.
Abstract : A series of ultra-light aerogels made of oxidized carbon nanotubes and cross-linked polyvinyl alcohol has been prepared by freeze drying of hydrogels, characterised, and tested as amine impregnated solid supports for CO2 capture. Abstract : A series of ultra-light aerogels made of oxidized carbon nanotubes and cross-linked polyvinyl alcohol has been prepared by freeze drying of hydrogels, characterised, and tested as amine impregnated solid supports for CO2 capture. The prepared spongy aerogels have demonstrated mechanical, chemical and thermal stabilities, and are electrically conducting. Polyethyleneimine impregnated aerogels with an amine content of 75–83% demonstrated CO2 capacity values ≥3.3 mmol g −1 in a dilute gas stream, which makes the prepared aerogels highly promising supports for amine impregnation in carbon capture applications.